2004
DOI: 10.1063/1.1649812
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on Ge condensation by thermal oxidation of SiGe-on-insulator structures

Abstract: The Ge depth profile and generation of dislocations associated with oxidation of SiGe-on-insulator (SGOI) substrates are examined from the viewpoint of the temperature dependence. It is found that Ge profiles in SGOI layers after oxidation are strongly dependent on the oxidation temperature. This fact is explained by the competitive process between the accumulation of Ge atoms at the SiGe/thermal oxide interface, determined by the oxidation rate, and Ge diffusion toward substrates during oxidation of SGOI subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 8 publications
1
49
1
Order By: Relevance
“…The strained Si on insulator (sSOI) structure is attractive for realization of high-performance complimentary metal-oxide-semiconductor field effect transistors (CMOS) due to the strain-enhanced carrier mobility and reduction of parasitic capacitance [1][2][3]. High temperature oxidation (N1100°C) process is usually used to induce Ge condensation process of SiGe/SOI structures, which is employed to fabricate strained Si on SGOI [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The strained Si on insulator (sSOI) structure is attractive for realization of high-performance complimentary metal-oxide-semiconductor field effect transistors (CMOS) due to the strain-enhanced carrier mobility and reduction of parasitic capacitance [1][2][3]. High temperature oxidation (N1100°C) process is usually used to induce Ge condensation process of SiGe/SOI structures, which is employed to fabricate strained Si on SGOI [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that there is a clear difference in the strain relaxation behavior between the two oxidation temperature recipe and that the oxidation at higher temperatures in the recipe A can lead to higher strain at a given Ge fraction, higher maximum strain values and higher Ge fraction at the maximum strain point, all of which are favorable in terms of the enhancement of the hole mobility in SGOI. This oxidation temperature dependence of the strain relaxation can be explained by the diffusion of Ge atoms segregated at SiO 2 /SiGe interfaces toward the SiGe/SOI substrates [12,13]. It has been reported that the activation energy of the Ge diffusion in SiGe layers, 5.8eV [14], is much higher than that of the oxygen diffusion in SiO 2 , 1.17eV [15], which determines the velocity of the movement of the SiO 2 /SiGe interface and the resulting generation rate of segregated Ge atoms at the interface during the Ge condensation.…”
Section: Ecs Transactions 33 (6) 501-509 (2010)mentioning
confidence: 99%
“…At higher oxidation temperature, the diffusion of Ge atoms surpasses the pile up of Ge atoms at the MOS interfaces due to the segregation associated with the oxidation of SiGe, resulting in the much smaller Ge concentration gradient and the flatter Ge fraction profile in SGOI. A lower temperature, on the other hand, the Ge profile becomes more abrupt, leading to the generation of dislocations and defects [12], which can cause the strain ECS Transactions, 33 (6) 501-509 (2010) relaxation. From this viewpoint, the oxidation temperature of as high as possible is better in maintaining the higher strain in SGOI.…”
Section: Ecs Transactions 33 (6) 501-509 (2010)mentioning
confidence: 99%
“…In order to improve the substrate crystal quality, the Si 0.7 Ge 0.3 substrates were prepared by the Ge condensation method using a 150 nm thick Si 0.85 Ge 0.15 film deposited on an 8-inch n-type Silicon-on-Insulator (SOI) wafer. The details of the fabrication process have been reported elsewhere [7]. Arsenic was implanted into all samples at 30 keV with a dose of 2×10 15 cm 2 and then activated at 1000°C for 5 s. After surface cleaning using H 2 SO 4 :H 2 O 2 =4:1 for 3 min followed by a 1 min dip in a…”
mentioning
confidence: 99%